Techniques for Masturbating: The Impossible Sexual Relationship as Prescribed by Gaspar Noé’s Film “We Fuck Alone” - Viktor Mazin (EJP import test, 2018)
Summary: This essay analyzes temporal-spatial differentiation in its relation to autoerotic sexuality. According to Nicolas Abraham, the principle for time/space différance is transfiguration of the interval’s regularity into rhythm. The analysis presented here is based on an examination of Gaspar Noé’s film We Fuck Alone. This film discloses the Lacanian maxim there is no sexual relationship in at least two respects. First, it demonstrates a fairly complex structure that might be called masturbating together alone. Second, this masturbating together alone includes not only a phantasmatic support, but also a prosthetic support that industrializes masturbation. Little girls masturbating about tomorrow. Little boys masturbating. Every second losing intensity, creating the need forever to go back inside and feel safe, to travel back and feel alive. It really is so difficult. – Genesis P-Orridge and Psychic TV, “A Hollow Cost,” 1994
Keywords: Espacement; Masturbation; Prosthesis; Supplément; time